TRANSFORMASI PROSES PEMBELAJARAN MENUJU KURIKULUM MERDEKA KELAS III SEKOLAH DASAR - Refiana Hidayah; Desi Susanti; Bambang Sumardjoko; Sabar Narimo (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to describe the transformation of the learning process during the implementation of the Independent Curriculum in third-grade students at Cipta Muda Public Elementary School, Buay Madang District, East OKU Regency. The focus of the study includes changes in learning approaches, the roles of teachers and students, and the obstacles and strategies implemented during the curriculum adaptation process. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results indicate that teachers have begun implementing project-based learning and differentiated learning based on student characteristics. The teacher's role has shifted from instructor to learning facilitator, while students become more active and independent. However, the implementation of the Independent Curriculum still faces obstacles, particularly in teacher readiness to develop independent learning modules and limited supporting facilities. This study concludes that the learning transformation towards the Independent Curriculum has progressed progressively, but requires ongoing mentoring, teacher training, and institutional support for optimal implementation. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan transformasi proses pembelajaran dalam implementasi Kurikulum Merdeka di kelas III SD Negeri Cipta Muda, Kecamatan Buay Madang, Kabupaten OKU Timur. Fokus penelitian meliputi perubahan pendekatan pembelajaran, peran guru dan peserta didik, serta kendala dan strategi yang diterapkan selama proses adaptasi kurikulum. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa guru mulai menerapkan pembelajaran berbasis proyek dan pembelajaran berdiferensiasi sesuai karakteristik peserta didik. Peran guru bergeser dari pengajar menjadi fasilitator pembelajaran, sementara peserta didik lebih aktif dan mandiri. Namun demikian, implementasi Kurikulum Merdeka masih menghadapi kendala, terutama pada kesiapan guru dalam menyusun modul ajar mandiri serta keterbatasan sarana pendukung. Penelitian ini menyimpulkan bahwa transformasi pembelajaran menuju Kurikulum Merdeka telah berjalan secara progresif, tetapi memerlukan pendampingan berkelanjutan, pelatihan guru, serta dukungan institusional agar implementasinya optimal.